Comparison study on reliability performance for polymer core solder balls under multiple reflow and HTS stress tests - Kar Y.B.; Hui T.C.; Agileswari R.; Lo C. (2023)
Drop ball reliability for Ball Grid Array (BGA) package on lead-free product is a major reliability concern. Integrating a polymer core in the solder ball could be a good strategy to dissipate stress better compared to the purely metallic solder ball. However, the diffusion rate of the copper is much faster than the diffusion rate of the solder. Hence, Kirkendall voids starts forming and causing crack between the interface of copper and solder. This could affect the solder joint as well as the solder ball drop reliability especially when subjected to high temperature stress. The new polymer core solder ball with 1 ?m thickness of nickel (Ni) coated on the copper (polymer core/copper/nickel/solder) could offer better solder ball joint and drop reliability performance. This work studies the effects of IMC growth, solder ball shear strength and drop test reliability. Subsequently, the failure modes were observed after multiple reflow (up to 5 times) and HTS stress tests. The IMC formation was observed under the high power scope with magnification 50 via the mechanical cross-section and was measured using an analytical software tool. Solder ball shear test was carried out to measure the solder joint performance after multiple reflow and HTS stress tests via the Dage 4000 series bond tester. Drop reliability test was carried out via the packing drop test. From this study, we could conclude that the polymer core solder ball with an additional Ni layer coating demonstrates better performance than the polymer core solder ball without Ni layer. The same observation applies to the solder ball shear strength, drop reliability performance in multiple reflow and HTS stress tests. The IMC thickness for polymer core solder ball without additional Ni layer is much thicker than the polymer core solder ball with an additional Ni layer, most probably because Ni could limit the Cu diffusion into the solder, thus resulting in better reliability performance. 2012 Elsevier Ltd. All rights reserved.